Exploring corneal endothelial cell dynamics: structure, functions and therapeutic approaches - Divya N. Pai; Srinivas P Sangly; Ashwija Shetty (Molecular Biology Reports, 2026)

Integrating INDOBLIGHTCAST forecasting with fungicide scheduling for sustainable management of potato late blight, Phytophthora infestans in southern India - Priyank Hanuman Mhatre; K.L. Divya; Santosh Watpade; S. Subhash; Praveen S. Patted; P. Janani; Aarti Bairwa; Sanjeev Sharma; Brajesh Singh (Crop Protection, 2026)

Assessment of design challenges and viability of wireless electric vehicle charging stations in residential setup to empower sustainable e-mobility: A comprehensive review - Anubhav Kumar Pandey; Nandini K․ K․; Suvetha P S; Abhinandan S Marashiddannavar; Divya Jaganath; Chandana Govindanayak; Anand Reddy (Next Research, 2026)

A Comprehensive Study on the Chemical, Biological, and Environmental Factors Shaping the Medicinal Value of Euphorbia hirta - J. B. Reshmi; P. S. Abitha; P. C. Divya; S. Grace Victoria; V. N. Meena Devi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2026)

Global research trends in full-depth reclamation for pavement engineering: a bibliometric analysis (1991–2025) - P. Divya; S. Shankar; Venkaiah Chowdary (Innovative Infrastructure Solutions, 2026)

Standardization of artificial inoculation technique for foot rot of finger millet caused by Sclerotium rolfsii and its validation using qPCR-based pathogen quantification - M. Bharath; H. R. Raveendra; Ravichandra; Mantesh Muttappagol; N. Sagar; Shadab M. Katib; Akash Bevanur; P. Yashwanth; Gutha Venkata Ramesh; Divya Bhandhari (Journal of Plant Pathology, 2026)

Bovine milk fat globules containing probiotics enhance colonisation resistance, pathogen exclusion and macrophage modulation in simulated gut environments - Arpita Das; Divya Singh; Rama N. Behera; Pranita P. Sarangi; Kiran Ambatipudi (Food Chemistry, 2026)

Microsatellite Markers Unveil the Genetic Tapestry of Milkfish Chanos chanos (Fabricius, 1775) in Indian Aquatic Realms - Divya Merin Jose; P. R. Divya (Biochemical Genetics, 2026)

Pollinia storage and viability assessment in Decalepis arayalpathra - S. Gokul; R. K. Divya; Anup S. Deshpande; P. Ravichandran; K. Ravikumar; M. K. Janarthanam; P. E. Rajasekharan; Pradeep Kumar Vishwakarma (Palynology, 2026)

Integrative network and structural analysis of Pinus derived phytosterols in diabetes associated pathways - P. Roshan Ali; Gutti Krishna Sri; Gojuvaka Sravanthi; Kavirayani Naga Lakshmi Shivani; Rajinikanth Sagapola; Kalasani Divya; V. V. Rajesham; Mitta Raghavendra; Dyvapu Lalitha Bhaskarini (In Silico Pharmacology, 2026)

Pac-rophage: Teaching Macrophage Phagocytosis Through Game Play - Caroline Cvetkovic; Madison C Fanning; Ali Ansari; Trisha Patnaik; Shreya Gustafson; Divya Bendigeri; Adam P Williamson; Elise A Corbin (Biomedical Engineering Education, 2026)

Sources of geogenic groundwater fluoride and associated health hazards in Pambar River basin of south India - C.N. Sridhar; T. Subramani; P. Divya; Zaixing Huang (Environmental Research, 2026)

Prebreeding using untapped rice genetic resources: linking the gap between biodiversity and crop improvement - Santhosh Venna; Divya Balakrishnan; P. K. Singh; B. Arun; Suneetha Kota; S. Amurutha Rao; Naresh Kumar Sahu; S.V. SaiPrasad; R. M. Sundaram (Journal of Crop Science and Biotechnology, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Selective recognition of ciprofloxacin by carbon quantum dots and their underlying mechanism - Divya Dagar; Bhim P. Kafle; Ankit Ladan; Venkatesan Shanmuganathan; Hsisheng Teng; Yuh-Lang Lee (Chemical Engineering Journal, 2026)

Integrating TRIGRS and RAMMS for the spatiotemporal prediction of rainfall induced landslides and landslide trajectory: a case study - A. Musaib; V. Aparna; P. V. Divya (Natural Hazards, 2026)

Toxicity and antiproliferative activity assessment of a novel compound Zr I isolated from Zingiber roseum Rosc - Swarnalatha P.; Deepika Divya K.; Anjali Jha; Anitha M.; S. P. D. Ponamgi; Seema Kumari; Sujatha Peela (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Genetic diversity assessment of near-threatened endemic catfish Clarias dussumieri in Western Ghats, India: implications for conservation - Divya Prema Radhakrishnan; Divya Merin Jose; C. P. Abhilash; V. S. Basheer; Uttam Kumar Sarkar (Hydrobiologia, 2026)

Isolation of microcrystalline cellulose from vegetable waste biomass and its potential as a high-performance green reinforcement in biocomposites - Indran Suyambulingam; Raja Somasundaram; Divya Divakaran; Senthilkumar Boominathan; P. Senthamaraikannan; Nadir Ayrilmis; Murni Handayani (Bioresource Technology Reports, 2025)

Chemical characterization and anticancer evaluation of Indian traditional rice Cultivars: Insights into their therapeutic potential - M. Udayamathi; P. Mohanapriya; S. Mahalakshmi; T. Subashini; S. Divya Sri; S. Pramila; A. Saravana Raj; Yuvaraj Dinakarkumar (Bioactive Carbohydrates and Dietary Fibre, 2025)

Wild species Oryza rufipogon as a potential donor for development of interspecific backcross population in the background of Samba Mahsuri (BPT5204) and detection of yield enhancing QTLs - M. Sridhar; C. Gireesh; Divya Balakrishnan; M. Sujatha; M. S. Anantha; C. H. Raveendra; P. Senguttuvel; D. Srinivasa Chary; V. P. Bhadana; R. M. Sundaram (Plant Physiology Reports, 2025)

Keeping an eye on climate change? Effects on vision health - Garima Singh; Divya Singh; Barry T Rouse; Pranita P Sarangi (Journal of Biosciences, 2025)

Unraveling allelic variations and population structure in wild species and cultivars of rice (Oryza spp.) for yield-related genes - Musku Sridhar; Divya Balakrishnan; M. S. Anantha; P. Senguttuvel; R. M. Sundaram; L. V. Subbarao; D. Aleena; Ch. Raveendra; S. Rathod; S. R. Chimmli; G. Padmavathi; M. Sujatha; et al. (Cereal Research Communications, 2025)

Novel Efficient Genome-Wide STR Panels for the Conservation of the Endemic Catfishes of Western Ghats: Critically Endangered Hemibagrus punctatus Jerdon (1849) and Vulnerable Horabagrus brachysoma (Günther, 1864) - P. R. Divya; Divya Merin Jose; Magdeline Christo; Charan Ravi; Uttam Kumar Sarkar (Biochemical Genetics, 2025)

Association of Urine Heavy Metals with Prevalence of Type 1 Diabetes and Poor Glycaemic Control - Samrat Ashok Vasudevan; Srinidhi Narayani Seenivasan; Avinash Kumar Raghupathy; Dinakaran Vasudevan; Parthasarathy Ayothi; Tanmayaa Nayak; Buvaneswari Gajendran; Karthika Durairaj; Divya Shree Sathish; Srilaxmi Balaji; Abisheak Kandasamy; P. Amaravathy; et al. (Biological Trace Element Research, 2025)

Cu-catalyzed click reaction in synthesis of eugenol derivatives as potent antimalarial agents - Jyoti; Divya Bhatt; Saurabh Kumar; Aransha Maurya; Anirban Pal; Mahendra P. Darokar; Dnyaneshwar U. Bawankule; Sudeep Tandon (Natural Product Research, 2025)

Isolation and characterization of xyloglucan endotransglucosylase/hydrolase (XET/XTH) provide insights on the functional evolution of XET family proteins in ginger (Zingiber officinale Roscoe) - Arshya Devi; Divya P. Syamaladevi; B. Mekha; K. S. Nehamol; I. P. Vijesh Kumar; T. E. Sheeja; D. Prasad (Genetic Resources and Crop Evolution, 2025)

Harnessing inter-subspecific genetic variability for hybrid rice improvement: analysis of genetic diversity, heterosis, and combining ability - K. Sruthi; K. B. Eswari; Ch. Damodar Raju; M. Sheshu Madhav; A. Dhandapani; M. Bala Satya Sree; K. Srikrishna Latha; P. Koteswararao; M. Sadath Ali; Divya Balakrishnan; P. Senguttuvel; Revathi Ponnuswamy; et al. (Euphytica, 2025)

Late Quaternary productivity and hydrographic variability in the upper water column of the Agulhas Return Current region as inferred from planktic foraminifera - Divya Verma; Pawan Govil; Shailesh Agrawal; P. Morthekai; Brijesh Kumar; Hidayatullah Khan (Quaternary International, 2025)

Evaluation of machine-learning algorithms in estimation of relative water content of sorghum under different irrigated environments - S. Divya Dharshini; Anurag; Anil Kumar; Satpal; Manoj Kumar; P. Priyanka; K. Pugazenthi (Journal of Arid Environments, 2025)

The Impact of Quality of Sleep and Effect of Sleep Apnea on Periodontal Health - Swathi Devarajan; P. Sreelakshmi; Divya Kumar; Deepak Moses Ravindran; Dhanadivya Krishnakumar; S. K. Balaji (Sleep and Vigilance, 2025)

Performance evaluation of existing and advanced processes for remediation of microplastics: A comprehensive review - Divya P. Barai; Swati L. Gajbhiye; Yogeshwary M. Bhongade; Hemant S. Kanhere; Dadasaheb M. Kokare; Nishikant A. Raut; Bharat A. Bhanvase; Sanjay J. Dhoble (Journal of Environmental Chemical Engineering, 2025)

Deep Learning in Analyzing Carbon Flux Patterns for Environmental Health: Remote Sensing Insights for Climate Mitigation Strategies - Hariharan Subramani; M. Neela Harish; Selva kumar S; P. Radhakrishnan; L. N. K. Sai Madupu; Kasturi Sai Sandeep; Divya Nimma (Remote Sensing in Earth Systems Sciences, 2025)

Corrigendum to “Characterization of renewable material from biowaste: Waste Albizia lebbeck leaves biomass-based bioplasticizer for futuristic applications” [J. Environ. Chem. Eng. 13 (2025) 115195] - Divya Divakaran; Indran Suyambulingam; Sunesh Narayanaperumal; P. Senthamaraikannan; H. Jeevan Rao; Thiago F. Santos; Caroliny M. Santos (Journal of Environmental Chemical Engineering, 2025)

Wild introgression lines of Oryza nivara as potential donor for yield and seedling vigour traits and mapping associated genomic regions - D. Sai Teja; Divya Balakrishnan; P. Magudeeswari; Sonali Kar; P. Arun Kumar; G. Pranay; R. Pushpa; Kalyani M. Barbadikar; L. V. Subba Rao; N. Sarla; S. V. SaiPrasad; R. M. Sundaram (Euphytica, 2025)

Best Practices and Recommendations for Non-Liquid Matrices Bioanalysis - Faye Vazvaei-Smith; Wenkui Li; Omar S. Barnaby; Sanjeev Bhardwaj; Juyao Dong; Carolyne Dumont; Carmen Fernández-Metzler; Brian Geist; Mohamed Hassanein; Amanda Hays; Anna Ilinskaya; Eugene P. Kadar; et al. (The AAPS Journal, 2025)
The analysis of Non-Liquid Matrices (NLMs) can provide key information on many aspects in drug discovery and development. These include but are not limited to drug uptake and distribution, engagement and modulation, and target exposure. A thorough understanding of these aspects is fundamental to the progression of drug development. In many cases, such an understanding can only be achieved through quantitative analysis of NLMs. Such dependence can lead to bottlenecks in the drug development process—as the practices and regulations that govern bioanalysis of conventional liquid matrices typically cannot be directly applied to NLMs. This paper strives to fill this crucial gap. To this end, subject matter experts from across the industry, through the auspices of the AAPS Bioanalytical Community, have combined their collective best practices for NLM bioanalysis in this paper. Certainly, this endeavor came with challenges, the most prominent of which also serves as the impetus for this project, the lack of literature on NLM bioanalysis dealing with different types of NLM, analysis rigor, and best practices to draw from. This paper aims to serve as a comprehensive set of best practices drawn from the experiences of leading scientists across the industry—for NLM bioanalysis in drug development. Graphical Abstract

Allometric scaling and carbon sequestration in agroforestry species of the Western Himalayas: a model-based approach - Megha VR; R. Kaushal; Sadikul Islam; Uday Mandal; Harsh Mehta; Rajkumar; J. M. S. Tomar; Anand Kumar Gupta; Anupam Barh; Vishwal Madhav P; Vibha Singhal; Rajiv Pandey; et al. (Environmental Monitoring and Assessment, 2025)

Characterization of renewable material from biowaste: Waste Albizia lebbeck leaves biomass-based bioplasticizer for futuristic applications - Divya Divakaran; Indran Suyambulingam; Sunesh Narayanaperumal; P. Senthamaraikannan; H. Jeevan Rao; Thiago F. Santos; Caroliny M. Santos (Journal of Environmental Chemical Engineering, 2025)

Physiological traits and population dynamics of Schizothorax niger (Heckel, 1838): Insights from Dal Lake and the Jhelum River, Kashmir, Himalayan region - Narayanan Karthik; Farooz Ahmad Bhat; Imtiyaz Qayoom; N. Jayakumar; C. Sudhan; P. Seenivasan; Divya Meril; Ishrat Mohd; Asra Mattoo (Journal of Fish Biology, 2025)
This study examines the physicochemical characteristics, morphometric features, biometric growth parameters, biological indices, physiological parameters, and biochemical profiles of Schizothorax niger population. The physicochemical analysis revealed a maximum temperature of 12.93 ± 1.33°C and hardness of 156.53 ± 12.82 mg/L in Dal Lake, whereas the Jhelum River had a minimum level of 10.94 ± 1.12°C temperature and 128.31 ± 11.62 mg/L of hardness. Dal Lake had a neutral pH (7.5 ± 0.2) and lower dissolved oxygen (6.8 ± 0.4 mg/L) compared to the Jhelum River (pH 7.2 ± 0.3; dissolved oxygen 7.5 ± 0.5 mg/L). Morphometric analysis showed significant differences ( p b = 3.15) than the Jhelum River ( b = 2.98). Biological indices revealed gender‐based variations in the gonado‐somatic index (GSI) and hepato‐somatic index (HSI), with GSI being higher in Dal Lake (0.21 ± 0.02) and HSI in the Jhelum River (1.04 ± 0.09). Haematological and biochemical analyses showed significant differences in parameters such as haematocrit (Dal Lake: 29.2 ± 2.1%; the Jhelum River: 32.4 ± 1.8%), glucose (Dal Lake: 85.3 ± 5.4 mg/dL; the Jhelum River: 68.1 ± 4.2 mg/dL), and total protein (Dal Lake: 6.2 ± 0.4 g/dL; the Jhelum River: 5.8 ± 0.3 g/dL) between sites. These findings provide valuable insights into the physiological traits and population dynamics of S. niger , informing species‐specific conservation strategies and ecosystem management practices.

Novel Ti/rGO@ZnCr LDH derived MMO for photocatalytic conversion of atmospheric elements and organic pollutants into valuable resources - Prabagar Jijoe Samuel; Tenzin Thinley; Divya Vinod; Hosakote Shankara Anusha; Hemanth Vikram P R; Gurupadayya B M; Kotermane Mallikarjunappa Anilkumar; Manickam Selvaraj; Mohammed A. Assiri; Harikaranahalli Puttaiah Shivaraju (Journal of Environmental Chemical Engineering, 2024)

Geospatial assessment of agroforestry land use systems using very high-resolution satellite images and artificial intelligence - Shivam Trivedi; P. V. Vinod; B. Chandrasekaran; M. K. Nagashree; S. Rama Subramoniam; V. B. Manjula; Amrita Singh; J. K. Mani; Arun S. Suryavanshi; Sushilkumar B. Rehpade; Akash Goyal; N. R. Shankar Ram; et al. (Agroforestry Systems, 2024)

Identification and pathogenicity of mycoflora associated with leaf spot disease of Aloe vera - Divya Singh; V. P. Chaudhary; S. K. Singh; Shivam Singh; Jay Kumar Yadav; Harshita (Vegetos, 2024)

Modulating temperature for Cu2ZnSnS4 (CZTS) synthesis via hot injection method and studying the photocatalytic efficiencies for the degradation of rhodamine 6G and methylene blue pollutants - Valentina Nava Murillo; Darshana Rajput; J. Manríquez; Erika Bustos; Jose de Jesus Perez Bueno; Divya Singh; Harish Dubey; Carlos Eduardo Frontana Vazquez; S. Godavarthi; Zakaryaa Zarhri; Fabrizio Olivito; Ashutosh Sharma; et al. (Environmental Research, 2024)

Female Collegiate Athletes’ Concussion Characteristics and Recovery Patterns: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Jaclyn B. Caccese; Reid A. Syrydiuk; Thomas A. Buckley; Sara P. D. Chrisman; James R. Clugston; James T. Eckner; Elsa Ermer; Carrie Esopenko; Divya Jain; Louise A. Kelly; Allyssa K. Memmini; et al. (Annals of Biomedical Engineering, 2024)

Initial Mild Traumatic Brain Injury Characteristics and Recovery Patterns Among Females Across the United States Military Service Academies: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Elsa Ermer; Adrian J. Boltz; Jaclyn Caccese; Thomas A. Buckley; Kenneth L. Cameron; Sara P. D. Chrisman; Christopher D’Lauro; James T. Eckner; Carrie Esopenko; Tamerah N. Hunt; Divya Jain; et al. (Annals of Biomedical Engineering, 2024)

Quantifying abnormal writing kinematics in writer’s cramp using a novel software platform - Kavadisseril Vivekanandan Vysakha; Vineeth Radhakrishnan; Praveen James; B. Suresh Kumar; Ashish Anand Susvirkar; Gangadhara Sarma; Ajith Cherian; K. P. Divya; Syam Krishnan Nair; Asha Kishore (Acta Neurologica Belgica, 2024)

Efficacy of biological agent Lecanicillium lecanii for the management of coffee leaf rust in India - Divya K. Das; Santoshreddy Machenahalli; Madhu S. Giri; Ranjini A. P; N. Suryaprakash Rao; M. B. Shivanna (Indian Phytopathology, 2024)

Multi-environment testing revealed the effect of yield genes on the grain yield stability in diverse rice germplasm - Aleena Dasari; Divya Balakrishnan; Santosha Rathod; P. V. R. Rao; Laksminarayana R. Vemireddy; C. N. Neeraja; S. Vanisri; K. N. Ranjith; R. M. Sundaram; Jyothi Badri (Cereal Research Communications, 2024)

Exploring extended-spectrum beta lactamase resistance in Vibrio parahaemolyticus and Vibrio cholerae within the tropical mangrove ecosystem of southwest India - Gopika Sivan; Hridya V.K; Divya P Sukumaran; Mohamed Hatha Abdulla (Brazilian Journal of Microbiology, 2024)

Linkage mapping and quantitative trait loci detection for seedling vigor and grain size in advanced backcross introgression lines from wild accessions of Oryza nivara - P. Magudeeswari; Divya Balakrishnan; Yoshimichi Fukuta; Hiroki Saito; D. Saitheja; G. Pranay; R. Padmashree; Kalyani M Barbadikar; Jyothi Badri; P. Senguttuvel; K. Sruthi; D. Ladhalakshmi; et al. (Genetic Resources and Crop Evolution, 2024)

Fine mapping of interspecific secondary CSSL populations revealed key regulators for grain weight at qTGW3.1 locus from Oryza nivara - Malathi Surapaneni; Divya Balakrishnan; Krishnamraju Addanki; Venkateswara Rao Yadavalli; Arun Prem Kumar; P. Prashanthi; R. M. Sundaram; Sarla Neelamraju (Physiology and Molecular Biology of Plants, 2024)

Fortification in Jaggery for Anti-Oxidant and Neuroprotective Benefits: Standardization, Sensory Preference, and Chemometric Analysis - Amrat Pal Singh; Mausam Singh; Ramdas; Shraddha P. Rahate; Neerja Tiwari; Divya Bhatt; Dnyaneshwar U. Bawankule; Puja Khare; Karuna Shanker (Sugar Tech, 2024)

Stability analysis and genetic mapping for yield traits of rice wild introgression lines - N. P. S. De Silva; P. Magudeeswari; Divya Balakrishnan; V. Gouri Shankar; B. Kavitha; A. Krishnamraju; P. Prashanthi; K. Vaibhav; D. S. Chary; S. N. C. V. L. Pushpavalli; Sarla Neelamraju (Cereal Research Communications, 2024)

SIRT6 in Regulation of Mitochondrial Damage and Associated Cardiac Dysfunctions: A Possible Therapeutic Target for CVDs - K. P. Divya; Navjot Kanwar; P. V. Anuranjana; Gautam Kumar; Fathima Beegum; Krupa Thankam George; Nitesh Kumar; K. Nandakumar; Abhinav Kanwal (Cardiovascular Toxicology, 2024)

Synthesis, Structural, and Optical Properties of 2-(2-methyl 8-hydroxyquinoline) Magnesium Nanorods for Optical Display Systems - J. P. Suchitra; J. Christina Rhoda; V. Bharathi Devi; P. Divya; Helen Merina Albert (Journal of Fluorescence, 2024)

Analysis of Muscle Fatigue Progression Using Geometric Features of Surface Electromyography Signals and Explainable XGBoost Classifier - N. Punitha; K. Divya Bharathi; S. R. Manuskandan; P. A. Karthick (Journal of Medical and Biological Engineering, 2024)

Familial adult myoclonus epilepsy: a pragmatic approach - Ajith Cherian; K. P. Divya; A. R. Swathy Krishnan (Acta Neurologica Belgica, 2024)

Widening the clinical, radiological and genetic spectrum of autosomal recessive ataxia of Charlevoix-Saguenay in Indian patients - K. P. Divya; Ajith Cherian; Hemanga Kumar Dhing; Savith Kumar; Bejoy Thomas; Mohammed Faruq (Acta Neurologica Belgica, 2024)

Development of polymorphic microsatellite markers for genetic stock identification of green chromide, Etroplus suratensis using next generation sequencing technology - Magdeline Christo; Divya Merin Jose; P. R. Divya; M. U. Rekha; U. K. Sarkar (Conservation Genetics Resources, 2024)

Biometeorological analysis on the molecular incidence of babesiosis and ehrlichiosis in dogs - Y. Ajith; Sasi Adithya; Varuna P. Panicker; N. Athira; V. Beena; M. Saifudeen Safeer; P. Preena; A. R. Nisha; C. Divya; S. G. Sangeetha; C. G. Umesh; R. C. Sundararajan; et al. (Theoretical and Applied Climatology, 2024)

Resolving taxonomic ambiguity and distribution of Tremoctopus gracilis (Cephalopoda: Tremoctopodidae) based on molecular evidence - Kurichithara K. Sajikumar; Geetha Sasikumar; Divya Viswambharan; Summaya Rahuman; N. S. Jeena; Nedumpally Vineesh; C. P. Binesh; K. P. Said Koya; V. Mahesh; Prathibha Rohit; P. K. Asokan; Smruthu Mohan; et al. (Marine Biology, 2024)

Genomic selection: a revolutionary approach for forest tree improvement in the wake of climate change - Umesh Sharma; H. P. Sankhyan; Anita Kumari; Shikha Thakur; Lalit Thakur; Divya Mehta; Sunny Sharma; Shilpa Sharma; Neeraj Sankhyan (Euphytica, 2024)

Assessment of Heavy Metals in Agroecosystems of the Cauvery Delta Region, South India Using a Focal Species: The Pavo cristatus - Manjula Menon; Rangaswamy Mohanraj; K. R. Divya; N. P. Mohammedali (Proceedings of the Zoological Society, 2023)

Comprehensive selection signature analyses in dairy cattle exploiting purebred and crossbred genomic data - Sonali Sonejita Nayak; Manjit Panigrahi; Divya Rajawat; Kanika Ghildiyal; Anurodh Sharma; Subhashree Parida; Bharat Bhushan; B. P. Mishra; Triveni Dutt (Mammalian Genome, 2023)

Identification and validation of blast resistance Pi1 gene in the derived mapping population of rice variety, NLR34449 through molecular markers - Dasari Aleena; V. Padma; G. Rekha; M. S. Prasad; M. S. Madhav; E. Punniakoti; T. Dilip; P. Sinha; M. Kousik; M. A. Das; M. Anila; Lal Ahmmed; et al. (Indian Phytopathology, 2023)

Predicting subsurface classification in 2D from cone penetration test data - Divya Varkey; Michael A. Hicks; Abraham P. van den Eijnden (Transportation Geotechnics, 2023)

Environmental impact and health risk assessment due to coal mining and utilization - P. Gopinathan; T. Subramani; Sofia Barbosa; Divya Yuvaraj (Environmental Geochemistry and Health, 2023)

Neck shrivel in European plum is caused by cuticular microcracks, resulting from rapid lateral expansion of the neck late in development - Bishnu P. Khanal; Anil Bhattarai; Divya Aryal; Moritz Knoche (Planta, 2023)
Main conclusion Susceptibility to neck shrivel in European plum is due to cuticular microcracking resulting from high surface area growth rates in the neck region, late in development. Abstract Susceptibility to the commercially important fruit disorder ‘neck shrivel’ differs among European plum cultivars. Radial cuticular microcracking occurs in the neck regions of susceptible cultivars, but not in non-susceptible ones, so would seem to be causal. However, the reason for the microcracking is unknown. The objective was to identify potential relationships between fruit growth pattern and microcracking incidence in the neck (proximal) and stylar (distal) ends of selected shrivel-susceptible and non-susceptible cultivars. Growth analysis revealed two allometric categories: The first category, the ‘narrow-neck’ cultivars, showed hypoallometric growth in the neck region (i.e., slower growth than in the region of maximum diameter) during early development (stages I + II). Later (during stage III) the neck region was ‘filled out’ by hyperallometric growth (i.e., faster than in the region of maximum diameter). The second category, the ‘broad-neck’ cultivars, had more symmetrical, allometric growth (all regions grew equally fast) throughout development. The narrow-neck cultivars exhibited extensive radial cuticular microcracking in the neck region, but little microcracking in the stylar region. In contrast, the broad-neck cultivars exhibited little microcracking overall, with no difference between the neck and stylar regions. Across all cultivars, a positive relationship was obtained for the level of microcracking in the neck region and the difference in allometric growth ratios between stage III and stages I + II. There were no similar relationships for the stylar region. The results demonstrate that accelerated stage III neck growth in the narrow-neck plum cultivars is associated with more microcracking and thus with more shrivel.

Role of RhoG as a regulator of cellular functions: integrating insights on immune cell activation, migration, and functions - Shubham Kumar Rai; Divya Singh; Pranita P. Sarangi (Inflammation Research, 2023)

N-Glycoprofiling of immunoglobulin G and lactoperoxidase from sheep milk using LC-MS/MS - M. Sudarshan; V. Divya Shree; P. Jyothibai; B.S. Gnanesh Kumar (International Dairy Journal, 2023)

Panmictic stock structure of milkfish (Chanos chanos, Forsskål 1775) from Indian waters determined using mtDNA marker - Divya Merin Jose; P. R. Divya; Kuldeep K. Lal (Journal of Genetics, 2022)

Outbreak and Management of Serpentine Leaf Miner, Liriomyza huidobrensis (Blanchard) (Diptera: Agromyzidae), on Potato (Solanum tuberosum L.) Crop in India - Priyank Hanuman Mhatre; Shivaji Hausrao Thube; Om Navik; E. P. Venkatasalam; Sanjeev Sharma; Jagadeesh Patil; S. Subhash; K. L. Divya; Santosh Watpade; Thava Prakash Pandian; M. Abas Shah; Manoj Kumar (Potato Research, 2022)

Refining the risk of HTLV-1-associated myelopathy in people living with HTLV-1: identification of a HAM-like phenotype in a proportion of asymptomatic carriers - Daniel Harding; Carolina Rosadas; Sandra Maria Tsoti; Amanda Heslegrave; Molly Stewart; Peter Kelleher; Henrik Zetterberg; Graham P. Taylor; Divya Dhasmana (Journal of NeuroVirology, 2022)
Up to 3.8% of human T-lymphotropic virus type-1 (HTLV-1)-infected asymptomatic carriers (AC) eventually develop HTLV-1-associated myelopathy (HAM). HAM occurs in patients with high (> 1%) HTLV proviral load (PVL). However, this cut-off includes more than 50% of ACs and therefore the risk needs to be refined. As HAM is additionally characterised by an inflammatory response to HTLV-1, markers of T cell activation (TCA), β 2 -microglobulin (β 2 M) and neuronal damage were accessed for the identification of ACs at high risk of HAM. Retrospective analysis of cross-sectional and longitudinal routine clinical data examining differences in TCA (CD4/CD25, CD4/HLA-DR, CD8/CD25 & CD8/HLA-DR), β 2 M and neurofilament light (NfL) in plasma in ACs with high or low PVL and patients with HAM. Comparison between 74 low PVL ACs, 84 high PVL ACs and 58 patients with HAM revealed a significant, stepwise, increase in TCA and β 2 M. Construction of receiver operating characteristic (ROC) curves for each of these blood tests generated a profile that correctly identifies 88% of patients with HAM along with 6% of ACs. The 10 ACs with this ‘HAM-like’ profile had increased levels of NfL in plasma and two developed myelopathy during follow-up, compared to none of the 148 without this viral-immune-phenotype. A viral-immuno-phenotype resembling that seen in patients with HAM identifies asymptomatic carriers who are at increased risk of developing HAM and have markers of subclinical neuronal damage.

Expanding phenotype of ATP1A3 mutation - Ajith Cherian; J. Nandana; K. P. Divya; Sharath Chandra Shetty (Acta Neurologica Belgica, 2022)

MOG antibody-positive paraneoplastic myelopathy in breast carcinoma: the new culprit - Ajith Cherian; Sharath Chandra Shetty; K. P. Divya; Pranab Karipody Prabhakaran; Harini Pavuluri; Naveen Kumar Paramasivan (Acta Neurologica Belgica, 2022)

Seasonal forecasting of tropical cyclones over the Bay of Bengal using a hybrid statistical/dynamical model - C. T. Sabeerali; O. P. Sreejith; Nachiketa Acharya; Divya E. Surendran; D. S. Pai (International Journal of Climatology, 2022)
The post‐monsoon (October–November–December) tropical cyclone (TC) over the Bay of Bengal is one of the most devastating natural disasters causing economic and human losses over India and its neighbouring countries. This study discusses a hybrid statistical/dynamical model developed to forecast the post‐monsoon cyclone activities over the Bay of Bengal, where 80% of the TCs of the North Indian Ocean are originated. In the hybrid model, the coupled model CFSv2 predicts the large‐scale climate indices, and the principal component regression (PCR) model is used to relate these indices with the TC frequency. A solid concurrent relation between the cyclonic disturbance frequencies and various large‐scale variables is noted. The dynamical variable, for example, the zonal wind, acts as a precursor variable. We identified three concurrent predictors (ocean heat content over the Bay of Bengal, sea surface temperature (SST) over the Indian Ocean, and SST over the tropical central Pacific regions) and two precursor predictors (low‐level wind at equatorial Indian ocean and strength of upper‐level easterly jet over African coast) influencing the cyclonic disturbance frequencies over the Bay of Bengal. The concurrent predictors are calculated from the CFSv2 hindcast/forecast output and the precursor predictors are calculated from the reanalysis data. The predictors influencing the cyclonic disturbance over the Bay of Bengal are also influencing the cyclonic storms. Hence, the same predictors are used for developing a hybrid model for cyclonic disturbance and storm frequencies. A significant inter‐correlation among different predictors is observed and the PCR model avoids these inter‐correlations and, in this method, PCs are estimated on the predictors to make them orthogonal to each other. The hybrid model achieved a significant skill for seasonal cyclone forecast over the Bay of Bengal. Results suggest the potential for using the hybrid model for the operational seasonal forecasting of post‐monsoon cyclone activity over the Bay of Bengal.

Activated Hollow and Solid Carbon Spheres for Enhanced Removal Efficiency of Pharmaceutical Pollutants and Heavy Metals in Water - Devika Laishram; Divya Kumar; Vishav Kant; Bhagirath Saini; Kiran P. Shejale; R. Krishnapriya; Vikash C. Janu; Rahul Singhal; Rakesh K. Sharma (Water, Air, & Soil Pollution, 2022)

Interference of bio-control Trichoderma to enhance physical and physiological strength of sugarcane during Pokkah boeng infection - Raghvendra Tiwari; Kajal Chandra; S. K. Shukla; V. P. Jaiswal; Natarajan Amaresan; Abhay Kumar Srivastava; Asha Gaur; Divya Sahni; Rajesh Kumar Tiwari (World Journal of Microbiology and Biotechnology, 2022)

E-waste recycling practices: a review on environmental concerns, remediation and technological developments with a focus on printed circuit boards - Saurabh P. Tembhare; Bharat A. Bhanvase; Divya P. Barai; Sanjay J. Dhoble (Environment, Development and Sustainability, 2022)

In silico identification of potential inhibitors of MPS1 from edible mushroom (Pleurotus ostreatus) to prevent aneuploidy and tumorigenesis - Divya Mishra; Ashish Mishra; Pramod Katara; M. P. Singh (Journal of Proteins and Proteomics, 2022)

Yield Estimation of Cassava Using SIMCAS Model Over the Major Cassava Growing Regions in India - Divya K. Lekshmanan; Raji Pushpalatha; V. S. Santhosh Mithra; S. Sunitha; James George; M. Velmurugan; P. Ashok; N. V. Mhasker; K. D. Desai; R. Shiny; Gangadharan Byju (Agricultural Research, 2022)

Total hip replacement monitoring: numerical models for the acoustic emission technique - Remya Ampadi Ramachandran; Christine Lee; Lu Zhang; Supriya M. H; Divya Bijukumar; P. Srinivasa Pai; Kharma Foucher; Sheng-Wei Chi; Didem Ozevin; Mathew T. Mathew (Medical & Biological Engineering & Computing, 2022)

Genetic stock identification in Perna viridis (Linnaeus1758) from the Indian Peninsula by using microsatellite markers - P. R. Divya; Linu Joy; Sunitha Poulose; P. M. Elizabeth Jency; V. S. Basheer; A. Kathirvelpandian; Vindhya Mohindra; Kuldeep Kumar Lal (Molecular Biology Reports, 2022)

Cognitive outcome following bilateral subthalamic nucleus deep brain stimulation for Parkinson’s disease—a comparative observational study in Indian patients - Kshiteeja Jain; Remya Ramesh; Syam Krishnan; Krishnakumar Kesavapisharady; KP Divya; Sankara P. Sarma; Asha Kishore (Acta Neurologica Belgica, 2022)

Gender differences in progressive supranuclear palsy - Rohan R. Mahale; Syam Krishnan; K. P. Divya; V. T. Jisha; Asha Kishore (Acta Neurologica Belgica, 2022)

In-Silico Identification of Natural Compounds from Traditional Medicine as Potential Drug Leads against SARS-CoV-2 Through Virtual Screening - Sai Mithilesh; Divya Raghunandan; P. K. Suresh (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Multi-criteria Decision Analysis for Site Selection of Apple Crop Cultivation: Case Study of Nainital, Uttarakhand - Priyadarshi Upadhyay; M. P. S. Bisht; Divya Uniyal (Journal of the Indian Society of Remote Sensing, 2022)

Impact of polystyrene microplastics on major marine primary (phytoplankton) and secondary producers (copepod) - P. Raju; P. Santhanam; S. Sonai Pandian; M. Divya; A. Arunkrishnan; K. Nanthini Devi; S. Ananth; J. Roopavathy; P. Perumal (Archives of Microbiology, 2022)

Myelopathy due to fibrocartilaginous embolism: elephant in the room - K. P. Divya; Ajith Cherian; Naveen Kumar Paramasivan; Jaffar Vali Sayyed (Acta Neurologica Belgica, 2021)

Isolated cortical lingual palsy: a slip of the tongue - Jaffar Vali Sayyed; K. P. Divya; Ajith Cherian; Naveen Kumar Paramasivan; S. Krishna (Acta Neurologica Belgica, 2021)

Cerebral creatine deficiency: Black cat in the coal cellar - Ajith Cherian; K. P. Divya (Acta Neurologica Belgica, 2021)

Re-Description of Sillago malabarica, Silver Whiting from Southern Indian Waters - P. R. Divya; Rahul G. Kumar; Linu Joy; C. P. Rajool Shanis; V. S. Basheer; K. K. Lal (Thalassas: An International Journal of Marine Sciences, 2021)

Improvement of small seed for big nutritional feed - P. B. Kavi Kishor; S. Anil Kumar; Jalaja Naravula; P. Hima Kumari; Divya Kummari; Rajasheker Guddimalli; Sujatha Edupuganti; Appa Rao Karumanchi; Perumal Venkatachalam; Prashanth Suravajhala; Rathnagiri Polavarapu (Physiology and Molecular Biology of Plants, 2021)

Crop Simulation Models as Decision-Supporting Tools for Sustainable Potato Production: a Review - K. L. Divya; Priyank Hanuman Mhatre; E. P. Venkatasalam; R. Sudha (Potato Research, 2021)

C3G Regulates STAT3, ERK, Adhesion Signaling, and Is Essential for Differentiation of Embryonic Stem Cells - Vijay V. Vishnu; Bh. Muralikrishna; Archana Verma; Sanjeev Chavan Nayak; Divya Tej Sowpati; Vegesna Radha; P. Chandra Shekar (Stem Cell Reviews and Reports, 2021)
Summary C3G (RAPGEF1), engaged in multiple signaling pathways, is essential for the early development of the mouse. In this study, we have examined its role in mouse embryonic stem cell self-renewal and differentiation. C3G null cells generated by CRISPR mediated knock-in of a targeting vector exhibited enhanced clonogenicity and long-term self-renewal. They did not differentiate in response to LIF withdrawal when compared to the wild type ES cells and were defective for lineage commitment upon teratoma formation in vivo. Gene expression analysis of C3G KO cells showed misregulated expression of a large number of genes compared with WT cells. They express higher levels of self-renewal factors like KLF4 and ESRRB and show high STAT3 activity, and very low ERK activity compared to WT cells. Reintroduction of C3G expression in a KO line partially reverted expression of ESRRB, and KLF4, and ERK activity similar to that seen in WT cells. The expression of self-renewal factors was persistent for a longer time, and induction of lineage-specific markers was not seen when C3G KO cells were induced to form embryoid bodies. C3G KO cells showed poor adhesion and significantly reduced levels of pFAK, pPaxillin, and Integrin-β1, in addition to downregulation of the cluster of genes involved in cell adhesion, compared to WT cells. Our results show that C3G is essential for the regulation of STAT3, ERK, and adhesion signaling, to maintain pluripotency of mouse embryonic stem cells and enable their lineage commitment for differentiation. Graphical abstract

Dopa-responsive dystonia, DRD-plus and DRD look-alike: a pragmatic review - Ajith Cherian; Naveen Kumar Paramasivan; K. P. Divya (Acta Neurologica Belgica, 2021)

Occurrence and removal of antibiotics from industrial wastewater - D. Akhil; Divya Lakshmi; P. Senthil Kumar; Dai-Viet N. Vo; A. Kartik (Environmental Chemistry Letters, 2021)

Exploration of Heat Stress-Responsive Markers in Understanding Trait Associations in Wheat - P. B. Manjunatha; Nivedita Sinha; Hari Krishna; Divya Chauhan; Pawan Kumar; Ranjeet R. Kumar; Neelu Jain; P. K. Singh; G. P. Singh (Journal of Plant Biology, 2021)

Experimental Evaluation of Seaweeds Liquid Extracts as an Alternative Culture Medium on the Growth and Proximate Composition of Picochlorum maculatum - S. Bharathi; S. Dinesh Kumar; S. Sekar; P. Santhanam; M. Divya; N. Krishnaveni; M. Pragnya; B. Dhanalakshmi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

Color slices analysis of land use changes due to urbanization in a city environment of Miami Area, South Florida, USA - Y. Divya; P. Gopinathan; Krish Jayachandran; Ayad M. Fadhil Al-Quraishi (Modeling Earth Systems and Environment, 2021)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Neurotuberculosis: an update - Ajith Cherian; Kesi Chellappan Ajitha; Thomas Iype; K. P. Divya (Acta Neurologica Belgica, 2021)

Obstructive Sleep Apnea Comorbid with Late-Onset Kleine–Levin Syndrome: A Rare Condition - M. P. Divya; Akash Kumar; Shivam Gupta; Sudheer Tale; Lokesh Kumar Saini; Ravi Gupta (Sleep and Vigilance, 2020)

An update and perspectives on the use of promoters in plant genetic engineering - Divya Kummari; Sudhakar Reddy Palakolanu; P B Kavi Kishor; Pooja Bhatnagar-Mathur; Prasanth Singam; Vincent Vadez; Kiran K Sharma (Journal of Biosciences, 2020)

RECK and TIMP-2 mediate inhibition of MMP-2 and MMP-9 by Annona muricata - G Drishya; Jyotsna Nambiar; Sanu K Shaji; Muralidharan Vanuopadath; A Achuthan; Abishek Kumar; Ashna Alias; Ayesha Sherif; Catherine Joseph; P Divya; Damu Sunil Kumar; Chinchu Bose; et al. (Journal of Biosciences, 2020)

Genetics of Parkinson's disease - Ajith Cherian; K. P. Divya (Acta Neurologica Belgica, 2020)

Population connectivity and genetic structure of Asian green mussel, Perna viridis along Indian waters assessed using mitochondrial markers - P. R. Divya; P. M. Elizabeth Jency; Linu Joy; A. Kathirvelpandian; Rajeev Kumar Singh; V. S. Basheer (Molecular Biology Reports, 2020)

Evaluation of genetic diversity of parental lines for development of heterotic groups in hybrid rice (Oryza sativa L.) - K. Sruthi; B. Divya; P. Senguttuvel; P. Revathi; K. B. Kemparaju; P. Koteswararao; R. M. Sundaram; Vikram Jeet Singh; E. Ranjith Kumar; Prolay Kumar Bhowmick; K. K. Vinod; S. Gopala Krishnan; et al. (Journal of Plant Biochemistry and Biotechnology, 2020)

Specific H+ level is crucial for accurate phosphate quantification using ascorbate as a reductant - Subramaniyan Divya; Peddisetty Sharmila; J. Dinakaran; Gupta Yamal; Kottapalli S. Rao; P. Pardha-Saradhi (Protoplasma, 2020)

Isolation and functional characterization of three abiotic stress-inducible (Apx, Dhn and Hsc70) promoters from pearl millet (Pennisetum glaucum L.) - Kummari Divya; P. B. Kavi Kishor; Pooja Bhatnagar-Mathur; Prashanth Singam; Kiran K. Sharma; Vincent Vadez; Palakolanu Sudhakar Reddy (Molecular Biology Reports, 2019)

Genetics of novel brown planthopper Nilaparvata lugens (Stål) resistance genes in derived introgression lines from the interspecific cross O. sativa var. Swarna × O. nivara - S. Akanksha; V. Jhansi Lakshmi; Arun Kumar Singh; Yamini Deepthi; P. M. Chirutkar; Ramdeen; Divya Balakrishnan; N. Sarla; S. K. Mangrauthia; T. Ram (Journal of Genetics, 2019)

In silico prediction of short hairpin RNA and in vitro silencing of activin receptor type IIB in chicken embryo fibroblasts by RNA interference - P. Guru Vishnu; T. K. Bhattacharya; Bharat Bhushan; Pushpendra Kumar; R. N. Chatterjee; Chandan Paswan; K. Dushyanth; D. Divya; A. Rajendra Prasad (Molecular Biology Reports, 2019)

Preliminary Screening of Halophilic Microalgae Collected from Different Salt Pans of Tuticorin, Southeast Coast of India - S. Balakrishnan; P. Santhanam; S. Jeyanthi; M. Divya; M. Srinivasan (Proceedings of the Zoological Society, 2019)

Deciphering demographic history and fine-scale population structure of cobia, Rachycentron canadum (Pisces: Rachycentridae) using microsatellite and mitochondrial markers - P. R. Divya; Joy Linu; C. Mohitha; A. Kathirvelpandian; P. Manoj; V. S. Basheer; A. Gopalakrishnan (Marine Biodiversity, 2019)

Identification and feld evaluation of female sex pheromone of leaf-eating caterpillar, Opisina arenosella (Lepidoptera: Oecophoridae) - K. R. M. Bhanu; D. R. Hall; R. V. Awalekar; M. Chandrashekharaiah; T. N. Divya; M. S. Prabhakara; K. P. Jayanth (International Journal of Tropical Insect Science, 2018)

Overfishing and Climate Drives Changes in Biology and Recruitment of the Indian Oil Sardine Sardinella longiceps in Southeastern Arabian Sea - Vasant Kripa; Kolliyil S. Mohamed; K. P. Said Koya; R. Jeyabaskaran; D. Prema; Shelton Padua; Somy Kuriakose; P. S. Anilkumar; Preetha G. Nair; T. V. Ambrose; A. M. Dhanya; K. S. Abhilash; et al. (Frontiers in Marine Science, 2018)

Pancreatic Cancer: Current Status and Challenges - Amanda R. Muñoz; Divya Chakravarthy; Jingjing Gong; Glenn A. Halff; Rita Ghosh; Addanki P. Kumar (Current Pharmacology Reports, 2017)

The Neuropeptide Orexin-A Inhibits the GABAA Receptor by PKC and Ca2+/CaMKII-Dependent Phosphorylation of Its β1 Subunit - Divya Sachidanandan; Haritha P. Reddy; Anitha Mani; Geoffrey J. Hyde; Amal Kanti Bera (Journal of Molecular Neuroscience, 2017)

Spatio-Temporal Monitoring and Ecological Significance of Retrievable Pelagic Heterotrophic Bacteria in Kongsfjorden, an Arctic Fjord - Rupesh Kumar Sinha; K. P. Krishnan; Savita Kerkar; T. Divya David (Indian Journal of Microbiology, 2017)

Fate of dissolved oxygen and survival of fish population in aquatic ecosystem with nutrient loading: a model - O. P. Misra; Divya Chaturvedi (Modeling Earth Systems and Environment, 2016)

Molecular understandings on ‘the never thirsty’ and apomictic Cenchrus grass - Divya P. Syamaladevi; S. S. Meena; R. P. Nagar (Biotechnology Letters, 2016)

A novel PR10 promoter from Erianthus arundinaceus directs high constitutive transgene expression and is enhanced upon wounding in heterologous plant systems - M. Chakravarthi; Divya P. Syamaladevi; P. Harunipriya; Sruthy Maria Augustine; N. Subramonian (Molecular Biology Reports, 2016)

Characterization of microsatellite markers in silver pomfret, Pampus argenteus (Perciformes: Stromateidae) through cross-species amplification and population genetic applications - C. MOHITHA; LINU JOY; P. R. DIVYA; A. GOPALAKRISHNAN; V. S. BASHEER; MOHAMMED KOYA; J. K. JENA (Journal of Genetics, 2015)

The effect of climate and meteorological changes on particulate matter in Pune, India - Suman Yadav; O. Divya Praveen; P. Gursumeeran Satsangi (Environmental Monitoring and Assessment, 2015)

Physiological and Molecular Insights to Drought Responsiveness in Erianthus spp. - Sruthy Maria Augustine; Divya P. Syamaladevi; M. N. Premachandran; V. Ravichandran; N. Subramonian (Sugar Tech, 2015)

Molecular phylogenetics of three species of the genus Rastrelliger using mitochondrial DNA markers - V. S. Basheer; C. Mohitha; N. Vineesh; P. R. Divya; A. Gopalakrishnan; J. K. Jena (Molecular Biology Reports, 2015)

Co-localization of Disturbed Flow Patterns and Occlusive Cardiac Allograft Vasculopathy Lesion Formation in Heart Transplant Patients - Lucas H. Timmins; Divya Gupta; Michel T. Corban; David S. Molony; John N. Oshinski; Habib Samady; Don P. Giddens (Cardiovascular Engineering and Technology, 2015)

Overexpression of EaDREB2 and pyramiding of EaDREB2 with the pea DNA helicase gene (PDH45) enhance drought and salinity tolerance in sugarcane (Saccharum spp. hybrid) - Sruthy Maria Augustine; J. Ashwin Narayan; Divya P. Syamaladevi; C. Appunu; M. Chakravarthi; V. Ravichandran; Narendra Tuteja; N. Subramonian (Plant Cell Reports, 2015)

Regulation of Gβγi-Dependent PLC-β3 Activity in Smooth Muscle: Inhibitory Phosphorylation of PLC-β3 by PKA and PKG and Stimulatory Phosphorylation of Gαi-GTPase-Activating Protein RGS2 by PKG - Ancy D. Nalli; Divya P. Kumar; Othman Al-Shboul; Sunila Mahavadi; John F. Kuemmerle; John R. Grider; Karnam S. Murthy (Cell Biochemistry and Biophysics, 2014)

Structural basis of kinetic variations in Sucrose Phosphate Phosphatase (SPP) of rice and Anabaena unveiled through computational analysis - Divya P. Syamaladevi; Neethi Jayaraman; N. Subramonian (Journal of Plant Biochemistry and Biotechnology, 2014)

Mitochondrial ATPase 6/8 genes reveal genetic divergence in the Coilia dussumieri (Valenciennes, 1848) populations of north east and northwest coasts of India - A. Kathirvelpandian; A. Gopalakrishnan; W. S. Lakra; Gopal Krishna; Rupam Sharma; P. R. Divya; Raj Kumar; J. K. Jena (Molecular Biology Reports, 2014)

Resistance reaction of gene introgressed lines against rice blast (Pyricularia oryzae) disease - B. Divya; S. Robin; R. Rabindran; H. Manjunath; P. Valarmathi; A. John Joel (Australasian Plant Pathology, 2014)

5′ Regulatory region of ubiquitin 2 gene from Porteresia coarctata makes efficient promoters for transgene expression in monocots and dicots - Anna Philip; Divya P. Syamaladevi; M. Chakravarthi; K. Gopinath; N. Subramonian (Plant Cell Reports, 2013)

Evolutionary Relationship Between Available Homologous Sequences of Sucrose Phosphate Phosphatase (SPP) Enzyme - Divya P. Syamaladevi; Neethi Jayaraman; N. Subramonian (Sugar Tech, 2013)

From peptides to peptidomimetics: rational design of potential PKC-β II inhibitors - P. Sri Divya; Kapil Jain; M. Elizabeth Sobhia (Medicinal Chemistry Research, 2013)

Experimental study of the interspecific competition between two sibling marine herbivorous rotifers in relation to food availability and initial population density - S. P. Divya; K. Kathiresan; P. Asha; V. Sekar; R. Rajasekaran (Acta Oceanologica Sinica, 2012)

Fe3O4-PEI-RITC Magnetic Nanoparticles with Imaging and Gene Transfer Capability: Development of a Tool for Neural Cell Transplantation Therapies - Humphrey H. P. Yiu; Mark R. Pickard; Cristina I. Olariu; Stephen R. Williams; Divya M. Chari; Matthew J. Rosseinsky (Pharmaceutical Research, 2012)

Molecular characterization of eight Indian Snakehead species (Pisces: Perciformes Channidae) using RAPD markers - Ajaz Ali Bhat; M. A. Haniffa; P. R. Divya; A. Gopalakrishnan; M. James Milton; Raj Kumar; Bilal Ahmad Paray (Molecular Biology Reports, 2012)

16S rRNA-based bacterial diversity in the organic-rich sediments underlying oxygen-deficient waters of the eastern Arabian Sea - Baby Divya; Ammini Parvathi; P. A. Loka Bharathi; Shanta Nair (World Journal of Microbiology and Biotechnology, 2011)

2D and 3D QSAR analyses to predict favorable substitution sites in anilino-monoindolylmaleimides acting as PKCβII selective inhibitors - P. Sri Divya; Baljinder K. Grewal; M. Elizabeth Sobhia (Medicinal Chemistry Research, 2011)

Constitutive expression of mustard annexin, AnnBj1 enhances abiotic stress tolerance and fiber quality in cotton under stress - Kesanakurti Divya; S. K. Jami; P. B. Kirti (Plant Molecular Biology, 2010)

Adsorptive Potential of 2-Mercaptobenzimidazole-Immobilized Organophilic Hydrotalcite for Mercury(II) Ions from Aqueous Phase and Its Kinetic and Equilibrium Profiles - T. S. Anirudhan; P. S. Suchithra; L. Divya (Water, Air, & Soil Pollution, 2009)

Transgenic tobacco and peanut plants expressing a mustard defensin show resistance to fungal pathogens - T. Swathi Anuradha; K. Divya; S. K. Jami; P. B. Kirti (Plant Cell Reports, 2008)

Numerical simulation by a stretched-coordinate Ocean General Circulation Model: A preliminary results - Arun Chakraborty; H. C. Upadhyaya; O. P. Sharma; Divya Jaisawal; S. K. Deb (Meteorology and Atmospheric Physics, 2003)

Covalent enzyme immobilization onto glassy carbon matrix-implications in biosensor design - P. Sree Divya; D. Savitri; Chanchal K. Mitra (Journal of Biosciences, 1998)